Engineering properties of asphalt binder modified with cup lump rubber - Norfazira, Mohd Azahar; Norhidayah, Abdul Hassan; Putra Jaya, Ramadhansyah; Mohd Rosli, Hainin; Che Puan, Othman; Nurul Athma, Mohd Shukry; Muhammad Azril, Hezmi (IOP Publishing, 2019)
olymers are being extensively used for modification of asphalt which yields several key benefits over conventional asphalt. Interest in using natural rubber polymer i.e. cup lump in asphalt modification has increased recently due to fluctuation in natural rubber prices and demand for improved asphalt properties. Since this current innovative road building technique is still new and there is limited information available on this topic, more studies are needed for better understanding the cup lump rubber modified asphalt (CMA). Therefore, this study investigates the engineering properties of the rubberised asphalt binder with 5, 10 and 15% cup lump rubber compared to conventional asphalt binder of 60/70 pen. Laboratory tests, i.e. penetration, softening point, ductility, viscosity, loss on heating and storage stability were performed and compared to the specification. From the results, the addition of cup lump rubber was found to harden the asphalt binder, produced low ductility, high softening point and viscosity resulting in less temperature susceptibility. Remarkably, 5% cup lump rubber gives better performance compared to other rubber percentages.